2019
DOI: 10.1016/j.msec.2018.10.077
|View full text |Cite
|
Sign up to set email alerts
|

Development of 3D-printed PLGA/TiO2 nanocomposite scaffolds for bone tissue engineering applications

Abstract: Porous scaffolds were 3D-printed using poly lactic-co-glycolic acid (PLGA)/TiO 2 composite (10:1 weight ratio) for bone tissue engineering applications. Addition of TiO 2 nanoparticles improved the compressive modulus of scaffolds. Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) revealed an increase in both glass transition temperature and thermal decomposition onset of the composite compared to pure PLGA. Furthermore, addition of TiO 2 was found to enhance the wettability of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(74 citation statements)
references
References 75 publications
2
68
0
Order By: Relevance
“…The morphology of TiO 2 nanomaterials (i.e., nanotubes) is, nevertheless, the most important factor in improving cell adhesion, proliferation, and differentiation [35,36]. A scaffold composed of polylactic-co-glycolic acid (PLGA) and TiO 2 nanoparticles as well as decorated glass with TiO 2 nanoparticles can improve the amount of precipitated calcium for bone regeneration compared to the scaffold without TiO 2 nanoparticles [206,207]. The adhesion and spreading of osteoblast cells with a complete integration can also be attained with composites made of polylactic acid (PLA), poly-ε-caprolactone (PCL), and TiO 2 particles or nanofiber meshes mimicking the bone regeneration properties [37,38].…”
Section: Tissue Regeneration and Chronic Wound Healingmentioning
confidence: 99%
“…The morphology of TiO 2 nanomaterials (i.e., nanotubes) is, nevertheless, the most important factor in improving cell adhesion, proliferation, and differentiation [35,36]. A scaffold composed of polylactic-co-glycolic acid (PLGA) and TiO 2 nanoparticles as well as decorated glass with TiO 2 nanoparticles can improve the amount of precipitated calcium for bone regeneration compared to the scaffold without TiO 2 nanoparticles [206,207]. The adhesion and spreading of osteoblast cells with a complete integration can also be attained with composites made of polylactic acid (PLA), poly-ε-caprolactone (PCL), and TiO 2 particles or nanofiber meshes mimicking the bone regeneration properties [37,38].…”
Section: Tissue Regeneration and Chronic Wound Healingmentioning
confidence: 99%
“…In the case of polymers added to the matrix, there are two different paths: co-polymers, formed by two or more monomeric species, and polymer–polymer blends, which involve a mixture of two polymers [ 27 ]. Among the co-polymers used in bone tissue engineering, poly(lactic-co-glycolic acid) (PLGA) [ 58 , 59 ] and poly(lactide-co-caprolactone) [ 60 , 61 ] are the most commonly used. Conversely, in the field of polymer blends, many studies are found on gelatin-polyvinyl pyrrolidone [ 62 ], gelatin-poly(lactide acid) [ 63 ], cellulose acetate-polycaprolactone [ 64 ], polyurethane/poly(lactic acid) [ 65 ], poly(lactide acid)/polycaprolactone [ 66 , 67 ], etc.…”
Section: Nanomaterials For Scaffoldsmentioning
confidence: 99%
“…Moreover, it was reported that TiO 2 on the three‐dimensional (3D) printed PLGA/TiO 2 construct could improve the ALP activity as well as HA formation of the osteoblast cells cultured on the nanocomposite for bone tissue regeneration. This could be due to the electrostatic interaction between the negatively charged Ti–OH and the Ca 2+ ion, which could trigger phosphate ions on the positively charged surface 252 …”
Section: Targeted Drug Delivery Systemsmentioning
confidence: 99%